Pengaruh Lingkungan Kerja dan Beban Kerja serta Budaya Organisasi Terhadap Kinerja Pegawai Dinas Kesehatan Samarinda - Muhammad Ahyar Ma’ali; Alexander Sampeliling (Indo Publishing, 2026)
This study aims to analyze the influence of the work environment, workload, and organizational culture on employee performance at the Samarinda City Health Office. The study used a quantitative approach with a survey method. The study population was 80 employees with a saturated sampling technique. Data collection was conducted through a questionnaire using a Likert scale. The data analysis technique used Partial Least Square-Structural Equation Modeling (PLS-SEM). The results showed that the work environment had a positive and significant effect on employee performance, workload had a negative and significant effect on employee performance, and organizational culture had a positive and significant effect on employee performance. The R-square value indicates that the independent variables are able to explain employee performance in the moderate category. This study provides implications that improving the quality of the work environment and organizational culture as well as optimal workload management can improve the performance of public sector employees